(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluating the changing knowledge about fall prevention for patients of nursing students at Thai Binh University of Medicine and Pharmacy after intervention. Methods: Intervention study was conducted in a group of 231 sophomore and junior nursing students of Thai Binh University of Medicine and Pharmacy with pre and post assessment from June 2023 to June 2024. Results: After the intervention, there was a change in the knowledge scores of nursing students in preventing falls for patients in all 4 domains, which increased significantly compared to before the intervention with p < 0,001 (the average score of knowledge about risk factors, risk assessment, fall prevention and management before intervention (TCT) was 3,6±1,5; 2,1±1,0; 3,5±1,1; 2,6±1,0 respectively, after intervention (SCT) increased to 5,5±1,2; 4,3±0,9; 6,6±1,3; 5,4±1,0 respectively). Conclusion: Nursing students’ knowledge about preventing falls for patients after the intervention improved in a positive direction compared to before the intervention. Therefore, fall prevention education programs should be developed and provided to nursing students to ensure that students have an accurate foundation of knowledge about fall prevention that will contribute significantly to the development of the profession, improving the quality of patient care and preventing risks related to patient safety, especially falls prevention.